Elastofibroma Dorsi: Clinicopathological Analysis of 71 Cases - Lococo, F.; Cesario, A.; Mattei, F.; Petrone, G.; Vita, L. M.; Petracca-Ciavarella, L.; Margaritora, S.; Granone, P. (The Thoracic and Cardiovascular Surgeon, 2013)
Introduction Elastofibroma dorsi (ELD) is a rare soft tissue benign tumor of the chest wall. So far, only a few large series have been reported in the English literature and, to the best of our knowledge, radiological assessment and clinical management remain without consensus. The aim of this study is to provide, on the basis of a single-institutional, homogeneous and large experience, ample evidences to support etiological and “clinical-usefulness-grade” classification hypotheses.Materials and Methods We report observational information on 71 ELD cases and, on the basis of these, we discuss the clinical onset features, radiological and surgical characteristics, as well as pathological and immunohistochemical evidences.Results In the period between January 1994 and September 2009, 71 consecutive patients (23 male and 48 female; mean age: 60.2 years; standard deviation [SD] ± 8.3 years) with ELD diagnosis were surgically treated at our institution. ELD was right sided in 34 patients (47.9%), left in 25 (35.2%), and bilateral in 12 (16.9%). In nine patients, ELD were diagnosed synchronously and three metachronously. Thirty-eight patients (53.5%) had no significant symptoms; 33 (46.5%) reported a clunking sensation or a localized scapular swelling during the shoulder movements. Sixty-six (93%) patients underwent surgical excision with radical intent while in five patients, a biopsy-only procedure was undertaken. Mean hospital stay was 3.0 days (SD ± 1.2 days) with a morbidity of 10.6% (one case of major postoperative bleeding requested a surgical revision of the hemostasis). At the univariate analysis, the probability of occurrence of morbidity increases with tumor size. All operated patients are alive and well at follow-up with no sign of recurrence and complete resolution of the symptomatology.Conclusions ELD is relatively uncommon, benign, and well controlled by radical surgery.
Keywords: elastofibroma dorsi; soft tissue tumors; chest wall tumors; elastin